New species of Scalibregmatidae (Annelida, Polychaeta) from the East Antarctic Peninsula including a description of the ecology and post-larval development of species of Scalibregma and Oligobregma - Blake, James A. (Zootaxa, 2015)
A large collection of scalibregmatid polychaetes from the east Antarctic Peninsula in May 2000 has yielded specimens of three new species of Scalibregma, Pseudoscalibregma, and Oligobregma. The new species of Scalibregma is represented by more than 400 specimens that include post-larval and juvenile forms which, for the first time, provide data on the sequence of development of key characters of a scalibregmatid. These data demonstrate that taxonomic characters including the form of the prostomium and presence of branchiae develop late in ontogeny and that small specimens cannot be reliably referred to a species or genus without a growth sequence. Juvenile morphology is also presented for the new species of Oligobregma. The new species of Scalibregma is compared with five northern hemisphere species and differs in details of the peristomium, upper and lower lips of the mouth, dorsal and ventral cirri, and nature of the short spinous setae of setiger 1. The new species of Pseudoscalibregma is unique in the nature of asymmetrical ventral cirri of posterior setigers. The new species of Oligobregma has large acicular spines in both noto- and neuropodia and these are present in juveniles. However, the final adult configuration of the prostomium is not evident until late in development. The taxonomic significance of the timing of development of post-larval and juvenile morphology elucidated in this study is discussed in relation to the validity of certain taxa and the current system of genera used in the family.